Substance abuse – An emerging problem among school-going adolescents of Jaipur, Rajasthan - Dobhal, Priyanka; Kashyap, Amita; Dobhal, Aviral; Mattas, Shalki (Asian Journal of Medical Sciences, 2022)
Background: Adolescents are a relatively healthy group, but their developmental stage makes them vulnerable to many risk‑taking behaviors. One such major issue is substance abuse. Aims and Objectives: This study aims to determine substance abuse behavior among school‑going adolescents of Jaipur city and factors associated with it. Materials and Methods: An observational, cross‑sectional study was conducted from July 2015 to February 2016. A total of 900 school‑going adolescents were enrolled from eight schools of Jaipur city and the Youth Risk Behavior Survey (YRBS) questionnaire was administered. Results: Most of the participants (67.56%) were in the age group of 13–16 years. Twelve adolescents out of 900 (1.34 %) in the given sample were taking drugs. Out of these, 66.67% took drugs 1 or 2 times in their life so far, while 33% took it 3–9 times. Majority 91.66% of the drug users were from government school (9 times more risk), 9/12 (75%) of the drug users were males. A total of 10% (90/900) of the study population were consuming tobacco. All of these adolescents smoke and 87.78% (79/90) chew tobacco. Conclusion: Although proportion seems less, yet the age at which these young students have been exposed to and indulged in substance abuse is a matter of concern.